Electronics and Communication Engineering - Digital Electronics - Discussion


The Boolean expression Y = (A + B + AB) C then Y will be equal to

[A]. AC
[B]. BC
[C]. C
[D]. none

Answer: Option C


No answer description available for this question.

K.Praveen Kumar Reddy said: (Mar 22, 2019)  
A+A'B = A+B.

then A+B'+A'B =A+B+B' = A+1 = 1,
therefore (A+B'+A'B) =1,
given that Y= (A+B'+A'B) C',
=>> Y =1.C' =C',
option C is correct.

Post your comments here:

Name *:

Email   : (optional)

» Your comments will be displayed only after manual approval.